2019
DOI: 10.3390/rs11101155
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Derived Bathymetry Using Machine Learning and Multi-Temporal Satellite Images

Abstract: Shallow water bathymetry is important for nautical navigation to avoid stranding, as well as for the scientific simulation of high tide and high waves in coastal areas. Although many studies have been conducted on satellite derived bathymetry (SDB), previously used methods basically require supervised data for analysis, and cannot be used to analyze areas that are unreachable by boat or airplane. In this study, a mapping method for shallow water bathymetry was developed, using random forest machine learning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 20 publications
2
93
0
Order By: Relevance
“…The multi-scene compositing approach addressed limitations inherent in conventional methods and reduced the impact of turbidity, performing better than the standard "pick the best scene" method that relies on a single image (Figures 3 and 4c vs. Figure 4a in Cape Lookout; and Figure 10e vs. Figure 10a,c in Saint Joseph Bay). The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The multi-scene compositing approach addressed limitations inherent in conventional methods and reduced the impact of turbidity, performing better than the standard "pick the best scene" method that relies on a single image (Figures 3 and 4c vs. Figure 4a in Cape Lookout; and Figure 10e vs. Figure 10a,c in Saint Joseph Bay). The final corrected SDB produced robust depths up to the limit of the lidar surveys, with typical errors ≤0.4 m. These excellent results from Sentinel-2 compared favorably with those produced in relatively low turbidity water in south Florida [22,44], and in regions with transparent waters [10,18,20,30]. Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19].…”
Section: Discussionmentioning
confidence: 64%
“…Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20]. However, our temporal compositing strategy successfully reduced the turbidity impact without requirement of visual inspection, thereby enhancing SDB performance in an easy way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations